2021
DOI: 10.1002/smll.202103448
|View full text |Cite
|
Sign up to set email alerts
|

Verification of Carrier Concentration‐Dependent Behavior in Water‐Infiltration‐Induced Electricity Generation by Ionovoltaic Effect

Abstract: Water‐infiltration‐induced power generation has the renewable characteristic of generating electrical energy from ambient water. Importantly, it is found that the carrier concentration in semiconductor constituting the energy generator seriously affect the electricity generation. Nevertheless, few studies are conducted on the influence of semiconductor carrier concentration, a crucial factor on electricity generation. Due to this, understanding of the energy harvesting mechanism is still insufficient. Herein, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…It was reported that the ionovoltaic effect was generated by a change in surface energy levels via ion dynamic motions. 32,33 Thus, the surface potential changes induced by the ion motions can partially contribute to the electric output. The AFM and KPFM images of the perovskite thin film under 55% RH were also measured and shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that the ionovoltaic effect was generated by a change in surface energy levels via ion dynamic motions. 32,33 Thus, the surface potential changes induced by the ion motions can partially contribute to the electric output. The AFM and KPFM images of the perovskite thin film under 55% RH were also measured and shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…12,[22][23][24] On the contrary, the established theory of ionovoltaics and the exploration of the voltage drop effect due to the 42 resistance of semiconductor electrodes were utilized as a fundamental theory for interpreting the core driving principle of the device. 48,54,[61][62][63][64] Thus, the theoretical hypothesis that the driving force behind continuous ionovoltaic generations based on evaporation/capillary phenomena is due to the change in carrier concentration in semiconductor electrodes was experimentally verified. [65][66][67] Therefore, to increase the efficiency of ionovoltaic sustainable energy generation, it is important to design nano/2D/ porous structured materials with large surface area and functional surfaces and to identify key elements that can control water flow inside the nanoscopic structure.…”
Section: Theoretical Aspectsmentioning
confidence: 99%
“…For the first time, the semiconductor carrier concentration-dependent behavior in water-infiltrationinduced power generation by ionovoltaic effect was investigated. 61 A porous semiconductor based on CuO nanowires was fabricated, and its electrical properties were controlled by atmospheric pressure plasma (APP) treatment (Figure 12A). [117][118][119][120] Increasing the carrier concentration of CuO nanowires by prolonging the APP time led to an improvement in the output performance of the waterinfiltration-induced ionovoltaic device (Figure 12B,C).…”
Section: Ionovoltaic Efficiency Enhancement: Tuning Electrical Proper...mentioning
confidence: 99%
“…The solid–liquid coupling shows a superior technology with high flexibility and eco-friendly development. So far, water-enabled electric generation developed is based on ion diffusion, flow potential, , evaporating potential, and ionovoltaic effect, , which are affected by the water–solid interface interaction. Among them, water transmission and evaporation-induced electricity stand out because they can operate independently in a wide range of environments without requiring mechanical input. The generator can generate sustainable electricity by the capillary action between water and solid surfaces when water passes through nano/micropores until the water completely evaporates. …”
Section: Introductionmentioning
confidence: 99%